Pola Penggunaan Ranitidine pada Pasien HIV & AIDS di UPIPI RSUD DR. Soetomo Surabaya - Nurohmawati, Weni; Triyono, Erwin Astha; Surdijati, Siti; Jaya, Halim Priyahau (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
HIV is a retrovirus that attacks CD4 lymphocyte cells. AIDS is a retrovirus disease caused by infection with retrovirus HIV-1 or HIV-2 which causes opportunistic diseases, secondary neoplasms and neurological abnormalities. In patients with HIV & AIDS often experience gastrointestinal disorders such as nausea and vomiting caused by side effects of the use of antiretroviral or due to other factors. Ranitidine is an H2 inhibitory receptor that will selectively and reversibly reduce excess gastric acid secretion. In this study ranitidine was used as a stress ulcer prophylaxis in hospitalized patients. This study aims to display ranitidine therapy data including type, dose, route of drug administration, prevalence, duration of use and qualitative analysis of interactions associated with medical record data at UPIPI RSUD Dr. Soetomo Surabaya. The research method used was observational prospectively on patient medical record with HIV & AIDS. Sampling was carried out by consecutive sampling period from November 1, 2016 to December 31, 2016. The results of this study give information that ranitidine was most widely used for stress ulcer prophylaxis therapy in hospitalized patients in UPIPI RSUD Dr. Soetomo Surabaya in a dose of 50mg / 2ml with a frequency of 2x1 while for oral ranitidine with a dose of 150mg / tablet with a frequency of 2x1. The use of ranitidine on HIV & AIDS patients in UPIPI RSUD Dr Soetomo Surabaya, related to dosage, route, frequency, interval, and duration of administration is in accordance with the existing guidelines.